The epidemiology and clinical features of Mycoplasma pneumoniae infection in neonates - Huang,Feng (2016)
Abstract Objectives This retrospective study was aimed to explore the epidemiological and clinical profiles of Mycoplasma pneumoniae infection in neonates. Methods From 2011 to 2014, 1322 hospitalized neonates with lower respiratory tract infections were screened for Mycoplasma pneumoniae by detection of Mycoplasma pneumoniae antibodies using Serion ELISA classic Mycoplasma pneumoniae kits. Results Mycoplasma pneumoniae was identified in 89 (6.7%) patients. The age ranged from 1 day to 28 days with a median of 22 days. The male to female ratio was 1.15:1. Mycoplasma pneumoniae infection peaked in spring (from March through May) and winter (from December through February). Compared with non-Mycoplasma pneumoniae infected neonates, those with Mycoplasma pneumoniae infection were older, presented fever more frequently, and had less tachypnea. Conclusions Mycoplasma pneumoniae could be an important etiologic agent for respiratory tract infection in neonates. In neonates Mycoplasma pneumoniae infection was usually associated with older age, presence of fever, and less tachypnea. Mycoplasma pneumoniae infection in neonates tends to be a mild process.